2014
DOI: 10.1080/15388220.2014.924074
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionality in Daily Metal Detector Student Searches in U.S. Public Schools

Abstract: While the effectiveness of metal detectors to improve school safety remains debated, many public schools continue to rely on this technology to control school violence. Among them is the 1% of public schools where students are searched on a daily basis by metal detector. This study examines the school-level risk factors associated with daily searches to estimate the disproportionality of their use in high-violence, majority-minority public schools. Analyzing data from the 2007−2008 School Survey on Crime and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Contrary to findings in Cuellar (in preparation), there was a significant positive correlation between authoritarian and educational/therapeutic strategies in the model. These findings are consistent with previous literature and research (Gastic & Johnson, 2014;Kupchick, 2010;Kupchik & Ward, 2014;Larsen, 2003;Servoss, 2014;Servoss & Finn, 2014;Warner, Weist, & Krulak, 1999).…”
Section: School Safety Strategiessupporting
confidence: 93%
See 3 more Smart Citations
“…Contrary to findings in Cuellar (in preparation), there was a significant positive correlation between authoritarian and educational/therapeutic strategies in the model. These findings are consistent with previous literature and research (Gastic & Johnson, 2014;Kupchick, 2010;Kupchik & Ward, 2014;Larsen, 2003;Servoss, 2014;Servoss & Finn, 2014;Warner, Weist, & Krulak, 1999).…”
Section: School Safety Strategiessupporting
confidence: 93%
“…In a systematic literature review, identified seven studies focused on effects of metal detectors on students, all of which utilized data from self-report surveys, and found that only one study provided limited support for their use in reducing the number of weapons brought into schools. Moreover, recent research by Gastic (2011) and Gastic and Johnson (2014) suggests that metal detectors compromise students' feelings of safety in United…”
Section: Summarizing Research On School Safety Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…What it is. Metal detectors and X-ray machines are used by school security staff to inspect students for weapons, which are confiscated if found (Gastic and Johnson, 2014). Metal detectors search for weapons on a person's body, whereas X-ray machines are used to inspect students' bags for weapons (Green, 2005).…”
Section: Technology #7: Metal Detectors and X-ray Machinesmentioning
confidence: 99%